PERAN ORANG TUA DALAM MENDIDIK IMAN KRISTEN KEPADA ANAK: Peran Orang Tua (ayah dan Ibu) - Solihin Nidin; Yonas PAP (AGUSPATI Research Institute, 2022)
Abstract Family is the first place children are. The role of parents is very important considering the responsibility of parents to shape children into God's will. Faith must be instilled as early as possible as the initial foundation for children to grow towards maturity. So that children understand what to do and what not to do. Basically God's word will be the basis of how the child will act. Parents have this important role, as representatives of God on earth. Children will see God through their parents in the family. In accordance with the existing problems, the purpose of writing this scientific paper is: to find out how much influence Christian faith has when children grow up, through the role of parents who instill it in children from an early age. In scientific writing, the author uses a qualitative method which aims to describe the role of parents in the family as a whole from all aspects. Keywords: Parents, Role, Christian education, children